2018
DOI: 10.1002/jor.23904
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of an in vivo turkey model for the study of flexor tendon repair

Abstract: Flexor tendon injuries are common and pose a clinical challenge for functional restoration. The purpose of our study was to assess the adequacy of the turkey as a large animal model for flexor tendon injuries in vivo. Twenty-four male turkeys underwent surgical flexor tendon cut and repair. Turkeys were allocated to five groups postoperatively: (1) foot casted in extension and sacrificed after 3 weeks; (2) foot casted in extension and sacrificed after 6 weeks; (3) foot casted in flexion and sacrificed after 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…More recently, Kadar et al established a turkey flexor tendon repair in vivo model and reported the details regarding turkey husbandry, anesthesia, surgical procedures, and postoperative care. Turkeys were housed in a kennel run with adequate space per animal and were subjected to perioperative management similar to mammals . With the successful development of turkey in vivo model, the isolation, and characterization of MSCs from the bone marrow is an essential step to extrapolate regenerative therapies from this novel preclinical large animal model for clinical management of flexor tendon injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Kadar et al established a turkey flexor tendon repair in vivo model and reported the details regarding turkey husbandry, anesthesia, surgical procedures, and postoperative care. Turkeys were housed in a kennel run with adequate space per animal and were subjected to perioperative management similar to mammals . With the successful development of turkey in vivo model, the isolation, and characterization of MSCs from the bone marrow is an essential step to extrapolate regenerative therapies from this novel preclinical large animal model for clinical management of flexor tendon injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Turkeys were housed in a kennel run with adequate space per animal and were subjected to perioperative management similar to mammals. 15 With the successful development of turkey in vivo model, the isolation, and characterization of MSCs from the bone marrow is an essential step to extrapolate regenerative therapies from this novel preclinical large animal model for clinical management of flexor tendon injuries. In this study, a population of plastic-adherent cells derived from 8-to 12-month-old heritage-breed turkey's bone marrow was identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tribology in other systems: Whilst tribology is important in synovial joints, other parts in the musculoskeletal system may also experience relative motions, such as the tendon. Friction in tendon repair was shown equally important [515]. Tribology at cellular levels: The effect of friction on cell behaviors was investigated in a number of studies [516,517].…”
Section: Tribology In Other Areasmentioning
confidence: 99%
“…With the exception of a single study in the rabbit forepaw, 2 in chickens, and 1 in a turkey, the majority of in vivo tendon healing studies have been performed in canine models. 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 However, canine studies are expensive and encounter significant regulatory limitations. We believe that this rabbit hindlimb model presents a new and exciting alternative model for future studies of tendon healing, although the correlation between rabbit and human tendon healing must be further studied.…”
Section: Discussionmentioning
confidence: 99%